The depiction of lungs and cardiac silhouette in the Saint Francis of Assisi with Angels by Sandro Botticelli (1445-1510) - Ashrafian, Hutan (Acta Biomedica Atenei Parmensis, 2022)
The Saint Francis of Assisi with Angels is considered a worldwide masterpiece painted by renaissance artist Sandro Botticelli. The painting reveals Saint Francis of Assisi surrounded by angels in a format that directly corresponds to lung anatomy and the cardiac silhouette. Together with previous evidence in Botticelli’s work, these findings add to the virtuosity and brilliance of Botticelli in depicting accurate human anatomy and highlight the role of topographical sciences and studying the human form for the presentation of both anatomical and abstract ideas in renaissance art.